Perbandingan Antara Suap dan Gratifikasi Terkait Penerapan Pasal 11 dan Pasal 12B UU TIPIKOR - Faiz Aulia Rahman; Irwan Triadi (Legtimacy: Journal of Law and Islamic Law, 2025)
This study examines the legal distinction and application between bribery under Article 11 and gratification under Article 12B of the Indonesian Anti-Corruption Law. Utilizing a qualitative method with a statute approach, the research analyzes statutory definitions and Supreme Court jurisprudence. Significant ambiguity exists due to overlapping elements, necessitating a clear differentiation between transactional bribery and gratification. The findings reveal that bribery requires a "meeting of mind" and explicit transactional intent. Conversely, gratification functions as disguised bribery, characterized by the absence of a formal consensus and, in specific cases, the application of a reverse burden of proof. Judicial patterns indicate that Article 12B serves as a preventive tool for latent corruption, while Article 11 acts as a repressive instrument for explicit transactions. Consistency in law enforcement is vital for establishing legal certainty and effectively eradicating corruption within the Indonesian legal system. Analysis underscores the critical importance of judicial consistency for justice.